1989
DOI: 10.1177/004728758902700402
|View full text |Cite
|
Sign up to set email alerts
|

A General Model Of Traveler Destination Choice

Abstract: Substantial evidence exists to support the proposition that consumer perceptions and preferences should be the basis for tourism marketing and consumerpolicy. Some of this evidence is reviewed, and a general model of traveler destination awareness and choice is presented. Results of an empirical test of the model provide some supportfor the hypotheses presented in the model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
579
1
34

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 897 publications
(625 citation statements)
references
References 13 publications
11
579
1
34
Order By: Relevance
“…As mentioned above, the relationship between destination images and intention to revisit is the scope of the present study, and the extant literature suggests that cognitive and affective images have a positive, direct effect on tourists' intentions to revisit a destination (Bigné, Sánchez, & Sanz, 2009;Chew & Jahari, 2014;, as positive perceptions of destinations drive purchase decisions (Woodside & Lysonski, 1989). Accordingly, our expectation is that: Fesenmaier (1997, p. 538) define holistic image as, "A composite of various products (attractions) and attributes woven into a total impression", while Um and Crompton (1990, p. 432-33) posited that holistic or overall image is, "A holistic construct which, to a greater extent, is derived from attitudes towards the destination's perceived tourism attributes".…”
Section: Intention To Revisit a Destinationmentioning
confidence: 96%
“…As mentioned above, the relationship between destination images and intention to revisit is the scope of the present study, and the extant literature suggests that cognitive and affective images have a positive, direct effect on tourists' intentions to revisit a destination (Bigné, Sánchez, & Sanz, 2009;Chew & Jahari, 2014;, as positive perceptions of destinations drive purchase decisions (Woodside & Lysonski, 1989). Accordingly, our expectation is that: Fesenmaier (1997, p. 538) define holistic image as, "A composite of various products (attractions) and attributes woven into a total impression", while Um and Crompton (1990, p. 432-33) posited that holistic or overall image is, "A holistic construct which, to a greater extent, is derived from attitudes towards the destination's perceived tourism attributes".…”
Section: Intention To Revisit a Destinationmentioning
confidence: 96%
“…Location choice models are applied to several other different contexts, such as the choice of a departure airport (Furuichi and Koppelman;1994), the choice of a hospital for patients by general practitioner (primary care physicians) (Whynes et al;, the choice of touristic destinations (Woodside and Lysonski;1989;Um and Crompton;1990;Eymann and Ronning;Oppermann;2000;Seddighi and Theocharous;Bigano et al;2006;Chi and Qu;Gössling et al; and in particular recreational outdoor facilities (Fesenmaier;1988;Scarpa and Thiene;2005;Thiene and Scarpa;2009), the choice of migrants (Fotheringham;1986) and the optimal allocation of charging stations for electric vehicles .…”
Section: Location Choicementioning
confidence: 99%
“…In a further 27% of the destinations, though generally known, respondents indicated that they needed more information in order to decide on visiting. It is important to note that destination awareness influences the tourists' purchase decision only if it forms part of the customer's awareness set and therefore determines the preference for a destination (Woodside and Lysonski, 1989;Um and Crompton, 1990). This therefore implies that such destinations falling within the unawareness set would naturally not be considered as potential vacation destinations to visit.…”
Section: Kenya's Tourism Marketing In Focusmentioning
confidence: 99%